Proses Dekomposisi untuk Pembuatan Serbuk Alumina dari Aluminium Format - Silvester Tursiloadi (Research Center for Chemistry - LIPI, 1999)
The high purity excellent chemical stability and mechanical properties, is quite important for alumina ceramic products. The alumina ceramic products was made from aluminium formate in this study. Decomposition of organic salts is a useful method for preparation of pure and fine ceramic powder without using of expensive metal alkoxides and without producing air pollution. The aluminium formate alt was prepared from reagent grade AlCl3.6H2O,AlCl3.6H2O was dissolved in H2O and then NH4OH was added to the solution. The white precipitates formed were washed with distilled water repeatedly, then dissolved in formic acid solution. Alumina powders prepared by decomposition of aluminium formate had high chemical purity and had small size of agglomerates with a narrow size distribution. The spesific surface area and the equivalent spherical diameter calculated from the value of spesific surface area were 60 m2/gr and 0.03um. The value of equivalent spherical diameter of Al2O3 powder in cumulative mass percent for finer particle were diameter (10%) of 1.7um and diameter (50%) of 5,5um. The average diameter of particles was 5.5um. For the alumina powders which was prepared by docomposition of aluminium formate, the x- Al2O3 and x- Al2O3 did not appear as intermediate phase between y- Al2O3 and a- Al2O3 when calcinated from 800°C to 900°C .However a- Al2O3 phase appeared at 800°C, so that this could reduce the transition temperature from y- Al2O3 to a- Al2O3. The single phase of a- Al2O3 was obtained after calcinating at 1100°C or more for 2 hours.